(untitled) (Journal of humanities and social sciences exploratio, 2025)
General verbs are a special category within the Chinese verb system. Characterized by vague semantics, flexible collocation, and a wide range of pragmatic functions, they are frequently used in daily communication but also pose significant challenges for learners of Chinese. This paper systematically reviews recent domestic and international studies on Chinese general verbs from four perspectives: dialectal research, semantic and pragmatic analysis, error analysis, and teaching Chinese as a foreign language. It summarizes the characteristics and limitations of existing research, and, in light of current trends in language studies, proposes directions for future research. The findings suggest that although substantial progress has been made, there is still ample room for development in terms of research perspectives, methodological integration, and theoretical framework construction.